Immunomodulatory Properties of Coriolus versicolor: The Role of Polysaccharopeptide - Saleh, Mohammad H.; Rashedi, Iran; Keating, Armand (Frontiers in Immunology, 2017)
Traditional uses of herbal medicine have depended mostly on anecdotal evidence for much of history. The increasing application of scientific rigor to the study some of these traditional therapies in recent years has revealed potent bioactivity, notably demonstrated by the 2015 Nobel Prize for the discovery of an anti-malarial compound from traditional Chinese herbs. Given the recent successes of immunotherapy and checkpoint blockade, there is a renewed interest in identifying new drugs with immunomodulatory effects. As an estimated 45-60% of cancer patients worldwide are reported to use complementary alternative medicine alongside traditional therapy, this review will highlight the literature on the immunomodulatory effects of one of these compounds. We report on the induction of a largely pro-inflammatory cytokine profile by the polysaccharopeptide (PSP) isolated from the Coriolus versicolor (Yun zhi) mushroom, as well as its effects on various immune subsets, and the clinical data that have led to its widespread adoption as an adjunct cancer therapeutic in many Eastern cultures. Particular focus is given to the potential mechanisms underlying the bioactivity of PSP and reports of its ability to promote antitumor immunity by helping overcome tolerogenic tumor microenvironments.